2006
DOI: 10.1021/jo052166u
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselectivity of Intramolecular SN‘ Cyclizations of Alkyllithium Reagents on Methoxy Alkenes

Abstract: The cyclization of alkyllithium reagents onto methoxy alkenes has been investigated. The alkyllithium reagent was generated by reductive lithiation of an alkyl nitrile. In an unbiased substrate, a methoxy leaving group attached to a stereogenic secondary carbon atom led to the cyclization product with high optical purity. The configuration of the product demonstrated that the cyclization had proceeded with high syn-S N ′ selectivity. Previously we have shown that 2-lithiotetrahydropyran regents cyclize to form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Rychnovsky and co-workers also described the generation of organolithium reagents by reductive lithiation of nitriles employing lithium di-tert-butylbiphenylide. Thus, they reported the generation and functionalisation of tertiary -amino organolithium reagents [140], that underwent intramolecular cyclisation onto an unsaturated carbon-carbon bond present in the molecule (see section 3.1) [93][94][95][96][97]. The Shapiro reaction [141] is a versatile method for transforming aldehydes and ketones into alkenyllithiums by reaction with a benzenesulfonylhydrazine and at least two equivalents of a strong base.…”
Section: Other Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rychnovsky and co-workers also described the generation of organolithium reagents by reductive lithiation of nitriles employing lithium di-tert-butylbiphenylide. Thus, they reported the generation and functionalisation of tertiary -amino organolithium reagents [140], that underwent intramolecular cyclisation onto an unsaturated carbon-carbon bond present in the molecule (see section 3.1) [93][94][95][96][97]. The Shapiro reaction [141] is a versatile method for transforming aldehydes and ketones into alkenyllithiums by reaction with a benzenesulfonylhydrazine and at least two equivalents of a strong base.…”
Section: Other Methodsmentioning
confidence: 99%
“…brief to allow a radical cyclisation, so the cyclisation proceeded through an alkyllithium intermediate [94]. In addition, the intramolecular 5-exo cyclisation of alkyllithium reagents onto methoxy allyl moieties was studied, showing that the process occurred with high selectivity [95]. Hence, the chiral alkyllithium 144, generated by reductive cleavage of a nitrile, underwent an intramolecular S N 2' cyclisation onto the methoxy allyl moiety with good enantioselectivity (>90% ee) [96].…”
Section: Addition To Carbon-carbon Double Bondsmentioning
confidence: 99%
“…We decided to carry out on 1c, the higher homologs of 1b, the reactions shown in Scheme 1, being aware that the presence of an extra methyl group on the allylic carbon on 1c will imply an extra stereochemical center at C-8 in addition to the existing ones, namely the benzylic C-2 carbon and the Δ [6][7] CC double bond (Scheme 3). We expected to be able to (i) generate on demand five-membered ring carbocycles with high absolute and relative stereocontrol, (ii) gain at the same time insight into the intimate mechanism of such process, and ultimately (iii) propose a model to predict the stereochemical outcome of any allylic substitution reaction (SN' reaction).…”
Section: Scheme 1 Schemementioning
confidence: 99%
“…13 Pr i R = t-Bu, Me Scheme 5 A mechanism has been proposed for the syn-S N allylic substitution of α-cyanoacetals with alkyllithium reagents. 14 The matched (9) and mismatched (11) substrates gave different products [98% (10) and 85% (12), respectively] when treated with lithium de di-t-butyl biphenylide (LiDBB) in THF at −78 • C as shown in Schemes 6 and 7. The spiroether effect is the controlling factor in determining the products.…”
Section: Allylic and Vinylic Substitutionsmentioning
confidence: 99%
“…For example, an investigation of the effect of changing the acid, the silyl triflate and the solvent showed that the bishomoepoxy alcohol (13) can be converted in high yield to the 6-endo-cyclic ether (15) rather than the normal 5-exo-cyclic ether (14) by reaction with trifluoromethanesulfonic acid, triisopropylsilyl triflate, and 2,6-lutidine in nitromethane (Scheme 8). 24 The regioselective production of the 6-endo-cyclic ether (15) is favoured when the partial positive charge is stabilized on a tertiary carbon and steric hindrance of the trialkyl silyl triflate leaving group in the transition state makes formation of the 5-exo-ether unfavourable.…”
Section: Reactions Of Cyclic Ethersmentioning
confidence: 99%